Fertility issues in women of childbearing age with spondyloarthritis - Bindoli, Sara; Cozzi, Giacomo; Lorenzin, Mariagrazia; Sfriso, Paolo; Doria, Andrea; Scagnellato, Laura; Ramonda, Roberta (Frontiers in Immunology, 2024)
The topic of fertility in women with spondyloarthritis (SpA) has been scarcely investigated to date.Recent systematic reviews and registry studies have brought renewed attention to the plight of women of childbearing age with rheumatic diseases, in particular SpA. Fertility may be impacted by physical impairment, hormonal imbalances and psychological distress. Several studies observed a reduction in anti-Müllerian hormone in women with SpA, reflecting a reduced ovarian reserve (OR).Furthermore, disease activity and the use of certain therapies can alter fertility, and this is reflected in a prolonged time-to-pregnancy (TTP), a validated outcome measure that can evaluate the status of subfertility. The employment of glucocorticoids or non-steroidal anti-inflammatory drugs has also been linked to reduced fertility, whereas the use of biologics, especially tumor necrosis factor inhibitors (TNFi), is not associated with a prolonged TTP. In all women of childbearing age with rheumatic diseases, preconception counselling is paramount, and a referral to a reproductive specialist should be considered in the presence of multiple factors that may influence fertility. A comprehensive evaluation involving a multidisciplinary team of rheumatologists, gynaecologists, and often psychologists is warranted. In this narrative review, we collected the currently available literature focusing on fertility issues in women affected by SpA, providing data on fertility outcomes, hormonal imbalance, and therapeutic concerns.